Effect of a Commercial Yeast-Based Product (Maxigen®) on Intestinal Villi Morphology and Growth Performance of Broiler Chickens - Fasina , Y.O.; Olowo, Y.L. (International Journal of Poultry Science, 2012)
Yeast products contain nucleotides that are essential for cellular functions and growth and may therefore enhance intestinal villi morphology and growth performance. Accordingly, two 42-day experiments were conducted to evaluate the efficacy of Maxigen® (a novel yeast-based product) in enhancing intestinal villi morphology, growth performance and flock uniformity. Experiment 1 utilized 480 (day-old) female chicks obtained from a commercial hatchery, weighed and randomly assigned to 2 dietary treatments. Treatment 1 (CX, control) consisted of chicks fed corn-soybean meal (SBM) diet that was not supplemented with Maxigen®. Treatment 2 (MG) consisted of chicks fed corn-SBM basal into which Maxigen® was added at 0.075% level. Each treatment consisted of 12 replicate pens, with each pen housing 20 chicks. On days 21 and 42 of experiment, growth performance (body weight and feed conversion) and flock uniformity were assessed. Experiment 2 was conducted in a similar manner, except that male chicks were used. Intestinal tissue samples were also collected on day 10 of experiment for histological evaluation of villi morphology. From the results, only Experiment 2 showed differences between CX and MG treatments for the parameters assessed. Specifically, at day 42, feed conversion ratio of birds in MG treatment (1.67) was superior (P